Comparative genomics of Nocardia seriolae reveals recent importation and subsequent widespread dissemination in mariculture farms in the South Central Coast region, Vietnam. Issue 7 (4th July 2022) - Le, Cuong T.; Price, Erin P.; Sarovich, Derek S.; Nguyen, Thu T. A.; Powell, Daniel; Vu-Khac, Hung; Kurtböke, D. İpek; Knibb, Wayne; Chen, Shih-Chu; Katouli, Mohammad
Abstract : Between 2010 and 2015, nocardiosis outbreaks caused by Nocardia seriolae affected many permit farms throughout Vietnam, causing mass fish mortalities. To understand the biology, origin and epidemiology of these outbreaks, 20 N . seriolae strains collected from farms in four provinces in the South Central Coast region of Vietnam, along with two Taiwanese strains, were analysed using genetics and genomics. PFGE identified a single cluster amongst all Vietnamese strains that was distinct from the Taiwanese strains. Like the PFGE findings, phylogenomic and SNP genotyping analyses revealed that all Vietnamese N. seriolae strains belonged to a single, unique clade. Strains fell into two subclades that differed by 103 SNPs, with almost no diversity within clades (0–5 SNPs). There was no association between geographical origin and subclade placement, suggesting frequent N. seriolae transmission between Vietnamese mariculture facilities during the outbreaks. The Vietnamese strains shared a common ancestor with strains from Japan and China, with the closest strain, UTF1 from Japan, differing by just 220 SNPs from the Vietnamese ancestral node. Draft Vietnamese genomes range from 7.55 to 7.96 Mbp in size, have an average G+C content of 68.2 % and encode 7 602–7958 predicted genes. Several putative virulence factors were identified, including genes associated with host cell adhesion, invasion, intracellular survival, antibiotic and toxic compound resistance, and haemolysin biosynthesis. Our findings provide important new insights into the epidemiology and pathogenicity of N. seriolae and will aid future vaccine development and disease management strategies, with the ultimate goal of nocardiosis-free aquaculture.